Pengaruh Total Ekspor, LIBOR, dan Upah Tenaga Kerja Terhadap Investasi Asing Langsung di Indonesia - Kresna Dewata, Bobby; Yogi Swara, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Indonesia seek funds for development to catch up with the development of the developed countries, both regionally and globally, therefore Indonesia has attempted to take advantage of foreign financing, the Foreign Direct Investment. This study intended to find out that the total exports, LIBOR and labor, as a variation (ups and downs) the value of foreign direct investment in Indonesia. Analysis techniques used in this study is the technique of multiple linear regression analysis, F-test for simultaneous testing and t-test for testing the partial. Results of data analysis showed simultaneous total exports, and labor LIBOR significant effect on foreign investment in Indonesia in 1990-2012, the results obtained by the F-test value F calculated (39.172)> F table (3.13) with a coefficient of determination (R 2 ) of 0.861 means that 86.1 percent of the variations (ups and downs) of foreign direct investment in Indonesia in 1990-2012 influenced by variations (ups and downs) of total exports, LIBOR and labor costs, while the remaining 13.9 percent are influenced by variations (ups and downs) other variables not included in the research model. Total exports of partial positive and significant effect, LIBOR has no effect, and labor and a significant negative effect on foreign direct investment in Indonesia in 1990-2012.
Keywords: investasi asing langsung; total ekspor; LIBOR; upah tenaga kerja